2022
DOI: 10.1007/s11356-022-23343-8
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone counteracts oxidative and inflammatory machinery in carrageenan-induced murine paw edema model

Abstract: Thymoquinone (TQ) is an active constituent in Nigella sativa, and is extensively reported for its distinguished antioxidant, and anti-in ammatory bioactivities. Despite the local protective response of the acute in ammation, it contributes to the development of various disease conditions such as cell death, organ damage, or genesis of tumors. Hence, in this study, the effects of orally administered TQ (50 and 100 mg/kg) for 14 days against edema development, oxidative stress, and in ammation were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…In recent research conducted by Hijazy et al [17], the effects of oral administration on the development of edema, oxidative stress, and inflammation in mice that had paw edema were investigated. Thymoquinone has been shown to reduce pro-inflammatory mediators in inflamed paw tissue, including IL-1, TNF-α, IL-6, MCP-1, C-reactive protein, myeloperoxidase, and NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…In recent research conducted by Hijazy et al [17], the effects of oral administration on the development of edema, oxidative stress, and inflammation in mice that had paw edema were investigated. Thymoquinone has been shown to reduce pro-inflammatory mediators in inflamed paw tissue, including IL-1, TNF-α, IL-6, MCP-1, C-reactive protein, myeloperoxidase, and NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…However, NO interacts with superoxide radicals at high concentrations, forming a powerful oxidant molecule, peroxynitrite, which causes severe cellular impairments. [39,40] The depleted endogenous antioxidants associated with MI induction may be due to their exhaustion and utilization for quenching ROS produced in response to ISO injection. [41] Significantly, PCA treatment inhibited the development of oxidative stress in the myocardium and decreased MDA, NO, and downregulated mRNA expression of nitric oxide synthase 2.…”
Section: Discussionmentioning
confidence: 99%
“…In recent research conducted by Hijazy et al [91], the effects of oral administration on the development of edema, oxidative stress, and inflammation in mice that had paw edema were investigated. The study found that thymoquinone reduced paw edema volume over time, lessened writhing movements caused by acetic acid, and decreased ear edema triggered by xylene.…”
Section: Thymoquinone's Effects On Inflammation and Immune System Mod...mentioning
confidence: 99%